Family-Centered Maternity Care And Its Effect On Self-Efficacy In Mothers: A Postpartum Blues Perspective - Ika Novita Sari; Hasibuan, Wilda Fasim; Nugrahani, Andita (Journal of health research and technology, 2026)
Introduction: Postpartum blues affect 50-80% of new mothers globally and can impact maternal-infant bonding if unaddressed. This study investigated the effectiveness of Family-Centered Maternity Care (FCMC) in enhancing maternal self-efficacy and reducing postpartum blues among postpartum mothers in Indonesian community health centers. Methods: A quasi-experimental study with pre-test and post-test control group design involved 60 postpartum mothers (30 intervention, 30 control) selected through purposive sampling. The intervention group received a four-week FCMC program including family support counseling, postpartum education, and family engagement activities. The control group received standard care. Maternal self-efficacy was measured using the Maternal Self-Efficacy Questionnaire (MEQ) and postpartum blues using the Postpartum Blues Questionnaire (PBQ). Data were analyzed using independent and paired t-tests. Results: FCMC significantly improved maternal self-efficacy in the intervention group (7.4-point increase, p < 0.001, Cohen's d = 2.37) compared to the control group (1.6 points, p = 0.136). Postpartum blues symptoms significantly decreased in the intervention group (6.7-point reduction, p < 0.001, Cohen's d = 1.87) versus the control group (0.9-point reduction, p = 0.522). Post-intervention, 63.3% of intervention mothers achieved high self-efficacy versus 16.7% in controls, while severe postpartum blues were eliminated in the intervention group.Conclusion Family-Centered Maternity Care effectively increases maternal self-efficacy and reduces postpartum blues in primary healthcare settings. The findings support integrating FCMC into standard maternal and child health services with emphasis on family involvement and comprehensive education programs.